PENERAPAN METODE KOLABORATIF UNTUK MENINGKATKAN KEAKTIFAN BELAJAR SISWA PADA MATA PELAJARAN IPAS DI KELAS V SD SWASTA GKPS 1 RAMBUNGMERAH - Wendi Leonardo Purba; Jubelando. O Tambunan; Alexander Samosir (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to describe the implementation of the collaborative learning method to enhance students' learning activeness in the subject of Science and Social Studies (IPAS) in Grade V of SD Swasta GKPS 1 Rambungmerah. The background of this research is the low level of student engagement during learning activities, as reflected in the lack of participation in discussions, reluctance to ask questions, and limited involvement in group work. This research employed a qualitative descriptive approach, with data collected through observation, interviews, and questionnaires distributed to both students and the IPAS teacher. The findings revealed that the application of collaborative learning fostered a more interactive and enjoyable classroom atmosphere, increased student participation in discussions, and promoted a sense of responsibility and cooperation within groups. Supporting factors included the teacher’s active involvement in designing suitable collaborative strategies and the availability of adequate learning facilities. Challenges encountered included varying levels of student confidence and differences in individual collaboration skills. This study is expected to serve as a reference for educators in developing more contextual and participative IPAS learning strategies.